DAMPAK DAYA TARIK FISIK (GOOD LOOKING) PRESENTER LIVE TIKTOK DALAM PENJUALAN PRODUK BATIK: STUDI KASUS UMKM 72BATIK INDONESIA - Alifiana Syifa Makhrodja; Ayunda Umi Putri Dewi Priyana; Anisa Putri Anggraini; Aqwamithoriq Ramadhan; Atika Rizki Septia (Universitas Muhammadiyah Surakarta, 2026)
The phenomenon of TikTok live streaming as a marketing medium has emerged as a new trend among UMKM, particularly in the traditional batik fashion sector. This study aims to analyze the extent to which the physical attractiveness (good looking) of hosts or presenters in TikTok live sessions influences consumers' purchase interest and buying decisions. Using a quantitative approach through a survey method targeting active TikTok consumers, preliminary findings reveal that appearance significantly correlates with engagement, trust, and sales conversion—especially in the traditional fashion product category like batik. These findings indicate that in modern marketing, visual aesthetics not only serve as initial appeal but also act as a powerful persuasive tool.